2010
DOI: 10.1021/ic1015274
|View full text |Cite
|
Sign up to set email alerts
|

A “Push−Pull” Mechanism for Heterolytic O−O Bond Cleavage in Hydroperoxo Manganese Porphyrins

Abstract: A water-soluble manganese porphyrin, 5,10,15,20-tetrakis-(1,3-dimethylimidazolium-2-yl)porphyrinatomanganese(III) (Mn(III)TDMImP) is shown to react with H(2)O(2) to generate a relatively stable dioxomanganese(V) porphyrin complex (a compound I analog). Stopped-flow kinetic studies revealed Michaelis Menton-type saturation kinetics for H(2)O(2). The visible spectrum of a compound 0 type intermediate, assigned as Mn(III)(OH)(OOH)TDMImP, can be directly observed under saturating H(2)O(2) conditions (Soret band at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 75 publications
5
85
0
Order By: Relevance
“…The nucleophilic addition of water to a doubly oxidized cobaltoxo intermediate is formally the microscopic reverse of the conversion of the manganese analog HOO-Mn III TDMImP to transdioxoMn V TDMImP that we have recently described (Scheme 3) (39,40). Here, both the hydroperoxo-manganese(III) complex and the oxo-manganese(V) complex were spectroscopically observed and the kinetics of the process could be analyzed in detail.…”
Section: Discussionmentioning
confidence: 95%
“…The nucleophilic addition of water to a doubly oxidized cobaltoxo intermediate is formally the microscopic reverse of the conversion of the manganese analog HOO-Mn III TDMImP to transdioxoMn V TDMImP that we have recently described (Scheme 3) (39,40). Here, both the hydroperoxo-manganese(III) complex and the oxo-manganese(V) complex were spectroscopically observed and the kinetics of the process could be analyzed in detail.…”
Section: Discussionmentioning
confidence: 95%
“…Although recent progress in solar energy research has led to an increased interest in photosynthesis and artificial photosynthesis [4,5], the structure of this cluster is still unknown [6][7][8][9] and very few manganese-based homogeneous catalysts have been reported to evolve oxygen upon oxidation [10,11]an observation that, however, has recently been questioned [12]. The ability to catalyze the heterolytic cleavage of the O-O bond in hydrogen peroxide and molecular dioxygen by manganese has been recently intensively studied [13]. Despite the mechanism of these processes catalyzed by heme oxygenases, such as cytochrome P450, cytochrome c oxidase, peroxidases, and catalase being known [14][15][16][17][18][19], direct observation of the O-O bond cleavage has been difficult due to the complex catalytic cycles, short-lived iron intermediates, and required cryogenic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mechanism of these processes catalyzed by heme oxygenases, such as cytochrome P450, cytochrome c oxidase, peroxidases, and catalase being known [14][15][16][17][18][19], direct observation of the O-O bond cleavage has been difficult due to the complex catalytic cycles, short-lived iron intermediates, and required cryogenic conditions. High-valent manganese oxo intermediates are more stable and can be functional analogs of heme proteins appearing in many biological systems using hydrogen peroxide and molecular dioxygen [13]. Recently, a bridged manganese(V) porphyrin dimer was shown to oxidize water into dioxygen, [20] and reversible O-O bond cleavage was observed for a manganese corrole system [21,22], and the design of novel, long-lived manganese(III) complexes, which can be a model of the precursor of the endogenous high-valent peroxo and oxo intermediates, has been published recently [23].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the para compounds are planar and, thus, favor intercalation within groves of nucleic acids, which may prevent their action and/or cause toxicity to normal tissue (18,220). Also, it would undergo oxidative degradation faster then ortho analog (30,128). Rawal et al just reported the tumor suppression in sc nude mouse xenograft model of human pancreatic cell line (220).…”
mentioning
confidence: 99%